Dynamic changes in circulating PD-1+CD8+ T lymphocytes for predicting treatment response to PD-1 blockade in patients with non-small-cell lung cancer. (January 2021) - Kim, Chang Gon; Hong, Min Hee; Kim, Kyung Hwan; Seo, In-Ho; Ahn, Beung-Chul; Pyo, Kyoung-Ho; Synn, Chun-Bong; Yoon, Hong In; Shim, Hyo Sup; Lee, Yong Il; Choi, Seong Jin; Lee, Yun Jeong; et al.
Abstract: Background: The predictive value of immune monitoring with circulating CD8 + T lymphocytes for treatment response to programmed cell death protein 1 (PD-1) inhibitors has not been explored in non-small-cell lung cancer (NSCLC), prompting us to investigate whether dynamic changes in PD-1 + CD8 + T lymphocytes have predictive value for durable clinical benefit (DCB) and survival after PD-1 blockade. Methods: Patients with recurrent and/or metastatic NSCLC treated with PD-1 inhibitors were enrolled (discovery cohort; n = 94). Peripheral blood was obtained immediately before and after one cycle of treatment with PD-1 blockade. Phenotyping of circulating CD8 + T lymphocytes was conducted using multi-colour flow cytometry. Predictive values of dynamic changes in circulating PD-1 + CD8 + T lymphocytes during the first cycle were validated in an independent cohort (validation cohort; n = 54) of a prospective trial with a PD-1 inhibitor (NCT03486119). Results: Circulating PD-1 + CD8 + T lymphocytes were enriched with effector/memory populations with elevated expression of activation- and exhaustion-related markers. Reduction in the frequency of PD-1 + cells among CD8 + T lymphocytes after one cycle of treatment was associated with a higher probability of DCB and superior survival outcomes in the discovery cohort. Similar results were obtained in the analysis of tumour antigen NY-ESO-1-specific CD8 + T lymphocytes and the validation cohort. Mechanistically, PD-1 molecule expression on CD8 + T lymphocytes suppresses the effector functions of tumour antigen-specific CD8 + T lymphocytes. Conclusions: Dynamic changes in circulating PD-1 + CD8 + T lymphocytes predict clinical, and survival benefit from PD-1 blockade treatment in NSCLC, providing a useful tool to identify patient subgroups who will optimally benefit from PD-1 inhibitors. Highlights: Current biomarkers for PD-1 blockade are suboptimal and require invasive procedures. Reduction of PD-1 + cells in CD8 + T lymphocytes predicts favourable treatment outcomes. Suppressive function of circulating PD-1 + CD8 + T lymphocytes was uncovered.